Socio-Demographic Factors And Compliance To Diabetic Health Education Among Diabetic Patients In A Tertiary Institution In Cross River State, Nigeria - Ella, Regina Etita; Lukpata, Felicia. Ekwok; Nwakwue, Ndukaku C.; Olayi, Emmanuel (Advances in Social Sciences Research Journal, 2018)
This study investigated the factors that affect compliance to diabetic health education among diabetic patients attending clinic in UCTH, Calabar. Three specific objectives were outlined out of which three null hypotheses evolved and tested. The study adopted the survey (descriptive) design in its approach. From the population of 191 patients that enrolled in the clinic, 119 purposively selected were involved in the study. A 26 item questionnaire constructed by the researcher was used in data collection. This was ascertained to be both valid and reliable. The data collected was analyzed using simple percentages, one-way ANOVA and independent t-test statistical tool. The level of significance was taken at 0.05 alpha level. Findings showed that the level of compliance of diabetic patients to diabetic health education is low ((46.2%); patients’ age (P> 0.05, F2 116 = 3.08), sex (P> 0.05, df = 117, critical t=1.97) and educational attainment (P> 0.05, F3, 115 =2.68) do not have significant influence on diabetic patients’ compliance to diabetic health education. While conclusion revolves around these findings, it was recommended among other things that nurses intensify their efforts in diabetic health education, evolve new strategies and seek to verify other factors that could hinder compliance.